1993
DOI: 10.2190/mncj-nb8e-m0wa-1fgm
|View full text |Cite
|
Sign up to set email alerts
|

Latina and African American Women: Continuing Disparities in Health

Abstract: Women of all races have faced incredible challenges as they sought to realize the promises of America. For women of color, these challenges were compounded by the second-class citizenship of U.S. racial and ethnic minority population groups. In an effort to assess the quality of life experienced by Latina and African American women, this article provides descriptive information on racial/ethnic differences in women's social conditions, health status, exposure to occupational and environmental risks, and use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…60 People of color have also historically had limited access to a variety of health care services, 61,62 including HIV-related medical services. For example, previous studies among people with HIV infection have found that non-whites are less likely to have outpatient visits and more likely to have emergency room visits than whites.…”
Section: Discussionmentioning
confidence: 99%
“…60 People of color have also historically had limited access to a variety of health care services, 61,62 including HIV-related medical services. For example, previous studies among people with HIV infection have found that non-whites are less likely to have outpatient visits and more likely to have emergency room visits than whites.…”
Section: Discussionmentioning
confidence: 99%
“…Other research persuasively hypothesized that African-Americans have a "life-course" deficit in access to medical care generally due to worse living standards, reflected in lower income and other SES indicators [23]. Race and social class, other research has shown, are interactive: racial discrimination exacerbates the healthdamaging effects of poverty for African-Americans [24][25][26]77]. In addition, African-American patients have fewer positive perceptions about their medical care than whites do.…”
Section: Racementioning
confidence: 99%
“…Male decisionmaking and social and financial power have been linked to child and female health across the globe (Lillie-Blanton et al 1993). This suggests that understanding gender relations within the Anosy region may be essential to improving overall health.…”
Section: Gendered Control Of Health Expendituresmentioning
confidence: 99%